The use of CMVIg rescue therapy in cardiothoracic transplantation: A single‐center experience over 6 years (2011‐2017). Issue 8 (20th July 2019) - Santhanakrishnan, Karthik; Yonan, Nizar; Callan, Paul; Karimi, Ebrahim; Al-Aloul, Mohamed; Venkateswaran, Rajamiyer
Abstract: Cytomegalovirus (CMV) is the most important infectious agent in solid organ transplant recipients and has a major impact on morbidity and mortality. Most cases are well managed with antiviral agents, but CMV hyperimmune globulin (CMVIg) can be used alongside antiviral therapy for prophylaxis in high‐risk thoracic organ recipients and to treat life‐threatening CMV infection or disease. CMVIg may also improve antiviral host defences when genetic resistance to antivirals or unwanted side effects occur. In this single‐center, retrospective study, we reviewed the CMVIg use to supplement antiviral therapy as a "rescue therapy" in cardiothoracic transplant recipients. These comprised 12 single lung, 11 double lung, and 12 heart transplant recipients. Patients received a median of 2 doses of CMVIg, most often in combination with ganciclovir or valganciclovir, and reduced immunosuppression. One week after rescue therapy was initiated, CMV DNA levels were significantly reduced, and after four weeks, CMV DNA was undetectable in 73% patients. Only one patient died as a result of CMV‐related disease. No significant adverse effects were observed. We conclude that CMVIg rescue therapy is safe, well tolerated, and effective at controlling viral replication in cardiothoracic transplant recipients.